ANALISA KINERJA DEMISTER SELAMA TAHUN 2019 DI PLTP LAHENDONG - Gisella Gabriella Tangkere; Rolles Nixon Palilingan; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Geothermal is now widely used by several developed countries, there are very many roles of geothermal energy sources, it is necessary to use one of them by utilizing geothermal heat energy itself into electrical energy. In chemical process industry there are a number of processes where a gas and a liquid come into contact with each other and whenever this happens, the gas will introduce a number of liquid particles. This liquid phase carried over to the gas phase can cause a number of problems such as equipment breakdown, process inefficiency etc, and need to be eliminated. Equipment used to remove entrainment is known as a Demister. This study aims to calculate Demister Efficiency throughout 2019 at PLTP Lahendong. Research conducted is to collect data at the Lahendong Geothermal Power Plant Unit-2 and this research uses data processing methods that use applications, namely steam tables and Microsoft Excel. Demister's performance in 2019 for 3 months got 88.90% J results which were influenced by heat loss, pressure and inner diameter, from results obtained after processing it can be concluded that the higher the heat loss value, better the efficiency value, Explains that performance Demister arguably had no problems in a year.